Rokeya Sakhawat Hossain and the Debate over Gender Relations among Muslim Intellectuals in Late Colonial Bengal - Sarkar, Binghamton University, USA, Mahua (Asiatic: IIUM Journal of English Language and Literature, 2013)
Rokeya Sakhawat Hossain was undoubtedly a remarkable intellectual and social reformer of her time, and in recent decades, her work has rightfully found its place among writings by â€œexceptional,â€ â€œearly feministâ€ women from colonial India. This paper is an attempt to situate Rokeyaâ€™s contribution as a writer and reformer within theÂ  larger context of debates over the â€œwoman questionâ€ as it unfolded in discussions ofÂ  Muslim intellectuals in late colonial Bengal. It proceeds from the premise that withoutÂ  such contextualisation, Rokeya and her work is too often cast as â€œout ofâ€ or â€œahead ofâ€Â  her time, when in fact Muslim intellectuals â€“ a number of women among them â€“ wereÂ  engaged in vibrant debates over a range of social and political issues in the first half ofÂ  the twentieth century that has been marginalised within normative histories of thatÂ  time.Â 